EXTENSIVE READING FOR TRANSLATION: ACQUIRING VOCABULARY FOR BETTER RENDITION - I Gusti Ngurah Agung Wijaya Mahardika (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Errors in translation stems from numerous sources, yet one of the mostcommon sources of the errors is the lack of vocabulary mastery. Therefore, it isimperative for aspiring translators to increase their vocabulary mastery. This articleproposed extensive reading through the implementation of book club inTranslation class to increase students’ vocabulary. The rationale for the book clubas well as the details of the implementation are discussed herein.